Asuransi Kebencanaan dalam Perekonomian Nasional dan Daerah - Tatok Djoko Sudiarto (Jurnal Universitas Paramadina, 2016)
AbstrakThe series of disasters that occurred late show is still much work to be completed by the various parties, namely the Government, Private / World of Business and Society. Included in this is the local society in terms of the decentralization policy, to reduce the risk and impact of disasters. One of the strategic effort should continue to be pursued in order to achieve disaster risk reduction program is to encourage people to "responsive and resilience" in disaster management.The impact of losses resulting from the emergence of huge losses predicted disaster, if then the entire risk of catastrophic losses that are charged only to the government, either through APBN (national level) and APBD (provincial and district level) can definitely be devastating to the performance of the government and posture as well as the health of the existing budget. This condition may eventually make the budget deficit, so as to reduce the burden that large budget caused by the disaster need to look for the best alternative, which can provide a solution without sacrificing the performance of the budget and the government efforts to improve the protection and welfare.One alternative option is to do the initiation of the need for disaster insurance for people living in disaster-prone areas, in an effort to transfer of risk financing and certainty of disaster impact protection for the community.Immediate steps for districts within the framework of autonomy and efforts to protect the public from threats, while improving the quality of life, particularly of the threat of disasters in the region, it is expected, and this step requires the political will of the holder of the mandate in the area, to realize the program of disaster insurance as one a safeguard for people in disaster-prone areas, especially if it will be focused for the poor. In this connection, data collection on poor people who are entitled to receive the insurance is the most important thing to ensure that the program with a limited budget, will be able to reach the right target and useful for people residing in vulnerable and high risk.